PENYUTRADARAAN PROGRAM DOKUMENTER DHUKUTAN : EKSISTENSI AGAMA JAWA - Fibriani, Lina Bayu; Sjafi'i, Achmad (Capture : Jurnal Seni Media Rekam, 2013)
This artwork describes about Javanesse culture existence which is applied into Dhukutantradition in the Nglurah society. Problems of this research are how Dhukutan tradition in theMenggung's sites as a Javanese existence indicated in documentary movie? Meanwhile, theconcept of directing is used observation,interview,and books as a reference.Then,the series ofresearch were developed into ideas in treatment namely story telling non linier and expository.This documentary movie uses four segments in the treatment 1) short introducing about Java inthe Dhukutan tradition; 2) religion and Dhukutan tradition as a phenomenon in Nglurah village;3) Dhukutan tradition process, and 4) Menggung's sites. In addition, informative is as adocumentary characteristic movie having traditional information in Nglurah. In the educationside,Javanese existence is applied in the Dhukutan.Keywords : Director, Dhukutan, Javanese religion, and documentary